Food subsidies in Egypts: Implications for the agricultural sector - von Braun, Joachim (International Food Policy Research Institute, 1988)
Food subsidies affect various sectors of the Egyptian economy, but their influence on agriculture, which employs a considerable share of the nation's resources, seems particularly strong (von Braun and de Haen, 1983). A major objective of this research was to analyze the agricultural policymaking in the environment of a large and growing food subsidy system. Inefficiencies and misallocation of resources in agriculture arising from food subsidies are hidden costs of such systems. However, it is crucial to separate out from the whole bundle of policy goals and related instruments those that are directly or indirectly linked to food subsidies. The basis for this can be provided only by a complete quantitative assessment of a country's agricultural policy and its determinants.